Win, rule and lose: contributions to understand the electoral performance of Peruvian incumbent parties - Mas Castillo, Luis (2014)
The article tries to explain the performance of peruvian incumbent parties in the immediate electoral process after their term. To do this, the limitations of two possible explanations are explored: retrospective voting and party institutionalization. Against this, the article proposes that, to explain the peruvian government parties poor performance, it is necessary to stressed the importance of the party leader and the presidential candidate. These are key factors that can affect the electoral chances of the Peruvian ruling party in a high caudillism.